3-Methyl-3-buten-1-ol (isoprenol) confers longevity and stress tolerance in Caenorhabditis elegans. (4th July 2019) - Pandey, Swapnil; Phulara, Suresh Chandra; Jha, Anubhuti; Chauhan, Puneet Singh; Gupta, Pratima; Shukla, Virendra
Abstract: The present investigation demonstrates the longevity-promoting effects of 3-methyl-3-buten-1-ol (isoprenol) in the animal model Caenorhabditis elegans that might be served as a lead nutraceutical in geriatric research. Our results showed that 0.5 mM isoprenol extended the mean lifespan of worms by 25% in comparison to control worms. Isoprenol also significantly enhanced survival of the worms under various stress conditions. It was found that the longevity-promoting effects of isoprenol were associated with improved age-associated physiological behaviour and reduced intracellular reactive oxygen species (ROS) accumulation. Finally, studies with gene-specific mutants revealed the involvement of pro-longevity transcription factors (TFs) DAF-16 and SKN-1 with simultaneous over-expression of GST-4 and SOD-3 in isoprenol treated worms. In silico analysis revealed the binding affinity of isoprenol with DAF-16 and SKN-1 TFs. Together, the findings suggest that isoprenol is able to enhance the lifespan of C. elegans and embarks its potential in the developments of formulations for age-related ailments.